The effect of non-monetary rewards on employee performance in massive open online courses - Pradorn Sureephong (2020)
© Kassel University Press GmbH. A challenge for organizations is to increase employee performance and motivation, since the most crucial asset of every organization is manpower. Many companies and factories have started implementing online training platforms under the concept of "Massive Open Online Courses (MOOCs)" in their workplace to foster employee performance. Previously, the mobile application called "HSC MOOC" which is provided by the Halal Science Center, Chulalongkorn University, Thailand functioned as a solution that encourages self-learning on online platforms at companies in Thailand. However, the main barrier or risk that occurs when implementing an online platform is the user's motivation, since the dropout rate is considered as a serious issue regarding MOOCs. Thus, incentive and reward were added to online training programs which aimed to motivate employees. Many types of rewards were provided for employees who had met their own company's expectations. Recently, psychology research papers have illustrated that non-monetary rewards seem to provide greater results on the side of employee's motivation. However, not all types of non-monetary rewards provide positive impact on employee's motivation. Therefore, the aim of this research is to present the effect of different nonmonetary rewards on employee performance. Ninety volunteer employees from a food manufacturing company in Chiang Mai, Thailand participated in this research. The experiment was divided into two sections. The first section aimed to measure the motivation of employees which based on different non-monetary rewards. The questionnaire for measuring Valence, Instrumentality, and Expectancy variables (VIE theory) was deployed to test employee motivation in 3 different groups; "Tangible Non-Monetary Rewards", "Social Non-Monetary Rewards" and "Job Related Non-Monetary Rewards". The test consisted of 10 items using a 5-point Likert scale. The second experiment aimed to reveal which type of non-monetary reward is the most suitable for motivating employees in participating and completing the course in MOOCs. Participants in different groups were assigned to learn via MOOCs on their mobile device within a period of 30 days. Different types of non-monetary rewards were provided only for participants who had completed certain conditions in MOOCs. The overall results showed that the group of tangible non-monetary rewards reached the significant highest score on the VIE questionnaire and over 60% of participants exposed to tangible non-monetary rewards completed the course's conditions in MOOCs.